Bullying Behavior among Students in Bandung - Ferdian, Dani; Hikmat, Rohman; Anshor, Abdullah; Irwan, Irwan; Triyanto, Triyanto (Universitas Pendidikan Indonesia, 2024)
Background: Bullying is an issue of serious concern in many school settings. Some forms of bullying are verbal, physical, or relational. Factors such as social pressure, diversity differences, and power inequality play a role in triggering bullying behavior among adolescents. The impact is not only limited to the victim, but also creates adverse interpersonal dynamics and affects the social climate in the school environment. Objective: to describe bullying behavior among students at SMPN 10 Bandung. Methods: This study used a quantitative descriptive approach. Sample selection from students of SMPN 10 Bandung. The sample was 104 students. Data collection was done through distributing questionnaires online using the Olweus Bully/Victim Questionnaire (OBVQ). Data analysis was carried out using descriptive statistics, focusing on univariate analysis to detail the incidence rate of bullying behavior. Results: the results showed that almost half of the respondents, 47 students, had high bullying behavior (45.2%). Bullying behavior can be verbal, physical, or relational. Bullying behavior can also be cyberbullying. The high percentage of respondents with high bullying behavior indicates the need for programs to prevent and reduce bullying behavior. Conclusion: health workers also have a role to make promotive and preventive programs to prevent bullying in students.